Investigating the relationship between visitor location and motivations to attend a museum. Issue 3 (26th May 2020) - Foster, Scott; Fillis, Ian; Lehman, Kim; Wickham, Mark
ABSTRACT: This paper investigates the role of visitor location and other related contributing factors in determining motivation to attend the Queen Victoria Museum and Art Gallery in the regional city of Launceston, Tasmania. It carries out an assessment of the literature on visitor motivation to attend museums and galleries, including visiting as a learning experience and as an environment for well-being. It also considers the role of visitor location in determining the factors behind the visit. Following our adoption of a visitor survey, this paper carries out a demographic visitor profile before considering our findings on geographical location, engagement with the museum and marketing engagement (including by visitor location). The study then carries out a series of independent t -tests with respect to visitor location, followed by ANOVA calculations with respect to the overall mean findings for different subgroups. Following this, confirmatory factor analyses determine item suitability, with four factors being identified. Following discussion of the findings and the drawing of conclusions, a series of recommendations for theory and practice are made, beginning with implications for QVMAG itself before broadening insight for other museums, galleries and cultural attractions more generally.